1993
DOI: 10.1093/genetics/134.4.1031
|View full text |Cite
|
Sign up to set email alerts
|

The mutational specificity of two Escherichia coli dnaE antimutator alleles as determined from lacI mutation spectra.

Abstract: In a companion study we have described the isolation of a series of mutants of Escherichia coli that replicate their DNA with increased fidelity. These mutants carry a mutation in the dnaE gene, encoding the alpha (polymerase) subunit of DNA polymerase III holoenzyme, which is responsible for the faithful replication of the bacterial chromosome. The mutants were detected as suppressors of the high mutability of a mutL strain (defective in postreplicative mismatch correction), in which mutations may be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is an interesting question whether other types of mutations, such as G. C + A e T transitions or the various transversions or frameshifts are also subject to the antimutator effect. Results described in detail in a companion paper (SCHAAPER 1993) suggest that for at least two of the antimutators, in the mutL background, both A . T + G.C and G-C -+ A .…”
Section: Discussionmentioning
confidence: 93%
“…It is an interesting question whether other types of mutations, such as G. C + A e T transitions or the various transversions or frameshifts are also subject to the antimutator effect. Results described in detail in a companion paper (SCHAAPER 1993) suggest that for at least two of the antimutators, in the mutL background, both A . T + G.C and G-C -+ A .…”
Section: Discussionmentioning
confidence: 93%
“…An important approach that significantly improved our understanding of the molecular mechanisms ensuring accurate replication of the bacterial chromosome is based on genetic selection and screening strains for altered fidelity (reviewed in [Fijalkowska et al., 2012 ]). Using this approach, several attempts were made to isolate mutations in the dnaE gene (Fijalkowska et al., 1993 ; Fijalkowska & Schaaper, 1993 ; Hiratsuka & Reha‐Krantz, 2000 ; Maki et al., 1991 ; Makiela‐Dzbenska et al., 2019 ; Oller et al., 1993 ; Oller & Schaaper, 1994 ; Sevastopoulos & Glaser, 1977 ; Sugaya et al., 2002 ; Vandewiele et al., 2002 ; Yanagihara et al., 2007 ), as well as genes encoding other pol III HE subunits (Fijalkowska & Schaaper, 1996 ; Gawel et al., 2008 , 2011 ; Oller et al., 1993 ; Pham et al., 2006 ; Schaaper, 1993 , 1996 , 1998 ; Taft‐Benz & Schaaper, 1998 , 2004 ) that conferred either antimutator or mutator phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of a series of dnaE mutants that result in an altered replication fidelity uncovered an important role of wild‐type pol III in contributing to the normally low replication error rates in E . coli (Fijalkowska et al., 1993 ; Fijalkowska & Schaaper, 1993 ; Oller & Schaaper, 1994 ; Schaaper, 1993 , 1996 , 1998 ). Mapping of the various mutations, which are spread throughout the entire dnaE gene, suggested that although some of them are potentially located close to the active site of the enzyme (Kim et al., 1997 ; Lamers et al., 2006 ; Parasuram et al., 2018 ; Pritchard & McHenry, 1999 ), the effect on replication fidelity was more often indirect.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, this appears not to be the case. Both in vitro and in vivo, misalignment mutagenesis specificity and frequency is strongly influenced by the DNA polymerase (RIPLEY and SHOEMAKER 1983;RIPLEY et al 1983;DE BOER and RIPLEY 1984;KUNKEL 1985a,b;FIX et al 1987;RIPLEY 1989, 1991;BEBEBNEK et al 1990;MASKER and CRISSEY 1993;SCHAAPER 1993).…”
mentioning
confidence: 99%